2021
DOI: 10.1007/s00429-021-02243-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural brain connectivity in congenital deafness

Abstract: Several studies have been carried out to verify neural plasticity and the language process in deaf individuals. However, further investigations regarding the intrinsic brain organization on functional and structural neural networks derived from congenital deafness is still an open question. The objective of this study was to investigate the main differences in brain organization manifested in deaf individuals, concerning the resting-state functional patterns, and white matter structuring. Functional and diffus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Findings of nine studies on adults (Ding et al, 2016; Cardin et al, 2018; Sinke et al, 2019; Bonna et al, 2021; Dell Ducas et al, 2021; Kumar et al, 2021; Andin & Holmer, 2022; Cardin et al, 2023; Ma et al, 2023) and one study on adolescents (Li et al, 2016) with C/PD were in support of the idea that cortical reorganisation following long‐term auditory deprivation is not limited to the auditory cortex and involves brain areas beyond the auditory cortex, which contribute to cognitive processing. In the Kumar et al (2021) study, stronger functional connectivity was observed between the auditory network and the Fusiform gyrus in prelingual deaf adults compared to control peers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings of nine studies on adults (Ding et al, 2016; Cardin et al, 2018; Sinke et al, 2019; Bonna et al, 2021; Dell Ducas et al, 2021; Kumar et al, 2021; Andin & Holmer, 2022; Cardin et al, 2023; Ma et al, 2023) and one study on adolescents (Li et al, 2016) with C/PD were in support of the idea that cortical reorganisation following long‐term auditory deprivation is not limited to the auditory cortex and involves brain areas beyond the auditory cortex, which contribute to cognitive processing. In the Kumar et al (2021) study, stronger functional connectivity was observed between the auditory network and the Fusiform gyrus in prelingual deaf adults compared to control peers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the right‐side lateralisation of RSFC might be a result of the functional reorganisation of the STG for visuospatial processing. Additionally, Dell Ducas et al (2021) reported greater changes in functional connectivity in the right hemisphere, particularly in frontoparietal and temporal lobes, in adults with congenital or prelingual deafness relative to their control peers. This observation is potentially modulated by the right‐side dominance of visuospatial processing in early auditory deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Efficient task performance was associated with stronger modularity in the task-negative DMN in terms of higher within-module connectivity in the DMN and lower between-module connectivity between the DMN and the task-relevant neural networks (Gonzalez-Castillo and Bandettini, 2017). It has been suggested that the DAN and the FPN, two task-critical networks supporting the egocentric task, show stronger functional and structural connectivity with the DMN in early deaf people (Dell Ducas et al, 2021; Li et al, 2022). Moreover, the increased inter-network connectivity between the task-irrelevant DMN and the task-relevant DAN and FPN was associated with impaired egocentric performance in congenitally deaf people (Li et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This approach was opted as we compared groups, and differences in brain responses, not specific to our manipulation, can therefore not be excluded. Many studies have indeed already indicated that deaf individuals develop functional and structural brain reorganisation, especially following cross‐modal plasticity (e.g., Alencar et al, 2019 ; Bottari et al, 2011 ; Cardin et al, 2020 ; Dell Ducas et al, 2021 ; Scott et al, 2014 ; Vachon et al, 2013 ). Given that such differences can be due to physiological (e.g., skull thickness, gyri folding, etc.)…”
Section: Methodsmentioning
confidence: 99%